The Potential of Spirulina platensis Biostimulan as a Seed Priming Agent to Enhance the Vigor and Viability of Cucumber Seeds (Cucumis sativus) - Rahmawati, Fitri Ayu; Pratiwi, Indah Wahyu; Samtani, Kariena; Atuillah, Nuning; Hidayatullah, Reza Aris; Ermawati, Netty; Sya'ban, Rahmat Ali; Kurniasari, Leli; Adnan, Moch. Rosyadi (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Spirulina platensis is a microalgae that can grow in waste media, including Sugar Mill Effluent (SME). In addition, Spirulina contains phytohormones that can be utilized to enhance seed germination. Cultivating microalgae will produce biomass that can be used for priming cucumber seeds. This research aims to determine the effect of Spirulina biomass and soaking time on the germination of cucumber seeds. In this research, a factorial Completely Randomized Design (CRD) was used, consisting of 5 levels of microalgae biomass concentration: control (untreated seeds), 0, 30, 45, and 60%, with soaking time of 3 levels: 1, 2, and 3 hours. The results demonstrated that Spirulina can grow in SME-based media, as indicated by the increase in size and density of microalgae cells. Analysis of the seed priming test results of 45% algae biomass concentration for 1 and 3 hours showed a significant effect on the parameter of vigor index, seed growth rate, and simultaneous seed growth. In the treatment with a 60% concentration and soaking time of 1, 2, and 3 hours, significant effects were observed on the parameters of MGT, vigor index, seed growth rate, and shoot length. Even though the 45% and 60% treatments showed no significant differences in the few parameters, the priming with Spirulina platensis exhibited no decrease in cucumber seed germination, these applications indicated no decrease in seed germination. This demonstrates that priming treatment with Spirulina platensis is not toxic to seedling growth.